EFEK KOMBINASI INFUSA DAUN SAMBILOTO, SALAM, KAYU MANIS, DAN RIMPANG TEMULAWAK TERHADAP KADAR HDL DAN LDL SERUM TIKUS WISTAR JANTAN MODEL HIPERGLIKEMIA - Wahyu Rhomadon (Jurnal Kedokteran Komunitas, 2018)
Introduction: Diabetes mellitus (DM) is associated with impaired fat metabolism which causes an increase in VLDL, LDL and decreased HDL. Sambiloto, bay leaves, cinnamon, and ginger rhizome (SSKT) have the potential for antihyperlipidemia, antioxidants and antihyperglycemia. This study aims to determine the potential of SSKT as antihyperglycemia in DM.Methods: Experimental laboratory in vivo with the control group post test only design using male Wistar rats aged 2-3 months. Mice were divided into five groups: negative control, positive control, and treatment group. The combination of infusion is given per sonde for 30 days at a dose of 125 mg / kg, 250 mg / kg body weight, 500 mg / kg body weight per day. Examination of HDL levels using the Abx Pentra HDL direct Pentra C200 device, while for LDL level examination using the Abx pentra LDL direct Pentra C200 device. The results of HDL data were analyzed using Kruskal Wallis, and LDL was analyzed using One Way ANOVA followed by Post Hoc LSD test. The results are said to be significant if (p <0.05).Result: STZ 25 mg and 10% HFD could not reduce HDL levels and increase LDL levels significantly. There were no significant differences between the positive groups with treatment of serum HDL and LDL levels.. There is a tendency that the higher dose of SSKT extract given will reduce serum LDL levels in hyperglycemia mice.Conclusion: The apropriation of SSKT infusion combination extract could not increase HDL levels and reduce serum LDL levels in hyperglycemic mice.